2011
DOI: 10.18632/oncotarget.213
|View full text |Cite
|
Sign up to set email alerts
|

miR-1 as a tumor suppressive microRNA targeting TAGLN2 in head and neck squamous cell carcinoma

Abstract: Based on the microRNA (miRNA) expression signatures of hypopharyngeal and esophageal squamous cell carcinoma, we found that miR-1 was significantly down-regulated in cancer cells. In this study, we investigated the functional significance of miR-1 in head and neck squamous cell carcinoma (HNSCC) cells and identified miR-1-regulated novel cancer pathways. Gain-of-function studies using miR-1 revealed significant decreases in HNSCC cell proliferation, invasion, and migration. In addition, the promotion of cell a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
161
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(173 citation statements)
references
References 36 publications
(55 reference statements)
7
161
1
1
Order By: Relevance
“…39 MiR-1, miR-133a, and miR-133b have been reported as significantly under-represented in leiomyosarcoma 40 and rhabdomyosarcoma. 11 There are reports of miR-1 in epithelial malignancies including non-small cell lung cancer, head and neck squamous cell carcinoma, and hepatocellular carcinoma, [41][42][43] but this has not yet been microRNA expression in human sarcomas PY Yu et al reported in non-myogenic sarcomas. The downregulation of miR-1 appeared to correlate inversely with the upregulation of Met in both non-small cell lung cancers and hepatocellular carcinomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 MiR-1, miR-133a, and miR-133b have been reported as significantly under-represented in leiomyosarcoma 40 and rhabdomyosarcoma. 11 There are reports of miR-1 in epithelial malignancies including non-small cell lung cancer, head and neck squamous cell carcinoma, and hepatocellular carcinoma, [41][42][43] but this has not yet been microRNA expression in human sarcomas PY Yu et al reported in non-myogenic sarcomas. The downregulation of miR-1 appeared to correlate inversely with the upregulation of Met in both non-small cell lung cancers and hepatocellular carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…In head and neck squamous cell carcinomas, miR-1 acts as a tumor suppressor by directly targeting transgelin-2, suggesting possible oncogenic pathways in the pathogenesis of head and neck squamous cell carcinoma. 42 Another miRNA of interest is miR-29. This miR functions as a positive regulator of myogenesis through feedback inhibition of YY1 and also functions as a tumor suppressor in rhabdomyosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Cell invasion assays were carried out using modified Boyden chambers consisting of Transwellprecoated Matrigel membrane filter inserts with 8-mm pores in 24-well tissue culture plates (BD Biosciences, Bedford, MA, USA), as described previously. 22 Screening of miR-143-and miR-145-regulated genes: Pathway analysis using databases. The predicted target genes and their miRNA binding site seed regions were investigated using TargetScan (release 6.2, http://www.targetscan.org/).…”
Section: Methodsmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are endogenous small ncRNA molecules (19)(20)(21)(22) bases in length) that regulate protein-coding gene expression by repressing translation or cleaving RNA transcripts in a sequence-specific manner. (5) Currently, 2578 human mature miRNAs are registered at miRBase (release 20, June 2013; http://www.mirbase.org/).…”
mentioning
confidence: 99%
“…Downregulation of miR-206 was previously found to contribute to laryngeal cancer proliferation and invasion via regulation of VEGF expression (34), while VEGF was reported to be a predictor for HNSCC (35), implying that miR-206 may be an inhibitor for HNSCC. A previous study found that miR-1 inhibited cell proliferation of HNSCC by targeting TAGLN2 (36), and downregulation of miR-153 promoted tumor metastasis in human epithelial cancer by targeting ZEB2 (37). On the other hand, nucleotide biosynthesis is involved with tumor cell growth during cell proliferation (38).…”
Section: Discussionmentioning
confidence: 99%